Pelatihan News Writing untuk Media Daring bagi Pegiat Badan Informasi Desa Sepit, Kabupaten Lombok Timur - Aurelius Rofinus Lolong Teluma; Muhammad Jamiluddin Nur; Novita Maulida (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Sepit Village in Central Lombok regency established the Village Information Agency (BID) in 2019, BID Pintar, to meet village information needs and assist internet-based governance. BID Pintar has published several village potentials such as MSME products and tourism potential. For improving the competence of youth and the editorial board of BID Pintar, this activity is carried out as additional knowledge and basic skills of news writing for online media, which include: understanding the value of news, reporting techniques and journalistic code of ethics; basic techniques of online news writing; and making simple illustrations or infographics. Activities are carried out using lecture, discussion, and practice methods which are directly evaluated. The evaluation results showed an increase in participants' knowledge about news values, reporting techniques, and journalistic codes of ethics. Meanwhile, in terms of skills, participants are generally indicated to be able to implement basic online news writing techniques, starting from making engaging titles, preparing news headlines or leads, applying the inverted pyramid principle, and using appropriate photos. To achieve an adequate online news writing ability, further training, both guided and independent, is needed, especially in the formulation of titles and leads and the use of simple and attractive illustrations